Mapping Research Trends on Agricultural Resilience in Publications from 2012 to 2024 - Loso Judijanto (West Science Agro, 2026)
This study aims to map the development of agricultural resilience research published between 2012 and 2024 using a bibliometric approach based on the Scopus database. By employing VOSviewer for network, overlay, and density visualizations, the study analyzes publication trends, collaboration patterns, and thematic structures within the field. The results show a significant increase in scholarly output over time, with climate change, agriculture, and food security emerging as the central pillars of the research landscape. Co-authorship and country collaboration networks indicate that the United States and India serve as major global hubs, supported by strong institutional clusters in China and growing contributions from African countries. The keyword co-occurrence analysis reveals a multidisciplinary structure integrating socio-ecological adaptation frameworks with agronomic and biological approaches. Overlay visualization suggests a recent shift toward molecular, genetic, and physiological studies addressing drought and abiotic stress, reflecting a growing emphasis on technological innovation. Agricultural resilience research demonstrates increasing integration across disciplines and regions, highlighting the need for balanced strategies that combine systemic adaptation, sustainability, and crop-level innovation to strengthen agricultural systems under climate uncertainty.